Methodological Techniques for Measuring Performance in the Hospitality Industry - NIKOLSKAYA, Elena Yurievna; KOVALEVA, Natalia Iosifovna; DRACHEVA, Elena Leonovna; GADIMOVA, Flora Kamalovna; NOVIKOVA, Nataliya Gennadievna (Journal of Environmental Management and Tourism, 2019)
This paper is devoted to enhancing existing methodological techniques for assessing performance in the hospitality industry. It is suggested that the efficiency of performance of businesses in the hotel industry depends on a number of objective and, to a certain degree, subjective factors. Analyzing these factors is crucial to developing efficient proposals aimed at fostering a proper competitive environment for enterprises in the hotel sector. The paper establishes that the diversity of criteria for measuring performance in the hospitality industry predetermines the need to single out those of them which can help put together integral assessments of the competitiveness of regions in terms of the development of the hospitality industry and cultivation of its attractiveness. It is proven that integral assessments can serve as guideposts in the choice of the more attractive regions to visit, the development of a business portfolio of tourism products across regions, and the evaluation of the effectiveness of regional policy on support for the development of the hotel sector, followed by the determination of ways to enhance its operation.